Comparing dental care coverage for older adults in eight jurisdictions. (30th September 2020) - Allin, S; Farmer, J; Quiñonez, C; Peckham, A; Marchildon, G; Panteli, D; Henschke, C; Fattore, G; Lamloum, D
Abstract: Background: Oral health is an important component of general health and healthy aging, yet financial protection for the costs of oral health care is often limited. Methods: We systematically compare dental care coverage in Australia (New South Wales), Canada (Alberta), England, France, Germany, Italy, Sweden, and the United States. Drawing on the WHO Universal Coverage Cube, we compare breadth (who is covered), depth (share of total costs covered), and scope (services covered), with a focus on adults aged 65 and older. We populated data collection templates to provide detailed and comparable descriptions of dental care coverage in 8 jurisdictions. Results: Overall there were four general types of coverage models: 1) deep public coverage for a small subset of the population based on strict eligibility criteria jurisdictions: Canada, Australia and Italy; 2) universal but shallow coverage of the population, combined with deeper coverage for a sub-set of the population meeting eligibility criteria: England, France, Sweden; 3) universal, and predominantly deep coverage for the whole population: Germany; and 4) shallow coverage available to some subgroups of the population in the United States. Conclusions: While age, specifically turning 65, is an important consideration in the design of public coverage in Canada, Australia and the United States, many jurisdictions do not consider age as an eligibility criterion for public coverage. Yet all jurisdictions we include, except Sweden, provide differential coverage for those who meet a specific low-income threshold. Due to the limited availability of comparable data within and across jurisdictions, further research would benefit from standardized data collection initiatives for oral health measures. Key message: Given the important role oral health plays in promoting healthy aging, the limited public coverage of oral health within statutory health systems warrants policy and research attention.